DOP78 Does KONO-S anastomosis reduce recurrence in Crohn's disease compared to conventional ileocolonic anastomosis ? A nationwide propensity score-matched study from GETAID Chirurgie Group (KoCoRICCO study). (30th January 2023) - Alibert, L; Betton, L; Falcoz, A; Manceau, G; Benoist, S; Zerbib, P; Podevin, J; Maggiori, L; Brouquet, A; Tyrode, G; Vuitton, L; Vernerey, D; et al.
Abstract: Background: The ileocolonic anastomosis is the main site of postoperative recurrence in Crohn's disease. In 2003, Kono et al. described a new operative technique that could reduce the rate of postoperative recurrence (Kono-S anastomosis). Recently, a randomized monocenter study showed a significant decrease in endoscopic recurrence rate at 6 and 18 months (22.2% vs 62.8% and 25% vs 67.4%), as well as a decrease in clinical recurrence ( Luglio. AnnSurg 2020 ). Nevertheless, the level of evidence remains too low to establish practice recommendations. The KoCoRICCO study aimed to compare outcomes between both techniques in two nationwide prospective cohorts. Methods: Adult patients with Crohn's disease requiring ileocolonic resection with Kono-S anastomosis (KA Group) were prospectively included in 7 french referral centers between 2020 and 2022. Patients with conventional side-to-side anastomosis (CA Group) were enrolled from a previously publish nationwide cohort (Maggiori et al. Ann Surg 2019). Comparisons between two groups were performed for postoperative morbidity in the overall population. To deal with confounding factors distributed inequally among groups, a propensity score analysis was performed in patients with available endoscopic follow-up to compare recurrence at first endoscopy in a matched 1:2 ratio population. Parameters involved in the propensity score were: sex, active smoking, history of bowel resection, penetrating and anoperineal disease, preop and postop biological therapy. Results: A total of 432 patients with ileocolonic anastomosis were enrolled, of whom 155 (35.9%) had a Kono-S anastomosis (Figure 1). Before matching both groups were unbalanced for preoperative, intraoperative and postoperative characteristics. Severe surgical morbidity according to Dindo-Clavien was 4.6% and 7.6% in the KA and CA groups, respectively (p<0.0001). In patients with available endoscopic follow-up, 61 patients in the KA group were matched with 122 in the CA group with the use of the propensity score. In the matched population, mean delay between surgery and endoscopic assessment was 7.4 months (SD ±3.0) and not statistically different between both groups. Endoscopic recurrence ≥ i2 was found in 29 patients (47.5%) and 54 patients (44.3%) in the KA group and CA group, respectively (p=0.6745). In unconditionnal logistic regression, Kono-S anastomosis was not associated with a lower risk of endoscopic recurrence: OR = 1.141 (95% CI 0.616-2.114, p=0.5147). Conclusion: Kono-S could be associated with reduced severe morbidity compared to a conventional side-to-side anastomosis in Crohn's disease but does not seem to reduce the risk of endoscopic recurrence. A longer follow-up is mandatory to assess a potential benefit on surgical recurrence.